Pengaruh Corporate Social Responsibility (CSR), Ukuran Perusahaan dan Nilai Perusahaan Terhadap Kinerja Keuangan (Studi Pada Perusahaan Yang Termasuk Dalam Indeks Saham Syariah IDX Growth Sharia Tahun 2021-2023) - Fachri Ramadhan, Hafidz; Budi Santoso, Suryo; Fakhruddin, Iwan; Pramono, Hadi (Journal of Accounting and Finance Management, 2025)
This study aims to examine the influence of Corporate Social Responsibility, Company Size and Company Value on Corporate Social Responsibility. The population in this study is companies included in the IDX Growth Sharia Sharia Stock Index listed on the IDX in 2021-2023, which is 30 companies. The sample of this study is 66 out of 30 companies. The research method used is quantitative. The analysis used was multiple linear regression analysis. The results of this study show that corporate social responsibility (csr) and company size do not have a significant effect on financial performance. The value of a company has a significant effect on financial performance.